Characteristics of the tinnitus and hyperacusis in normal hearing individuals - Urnau, Daila; Tochetto, Tania Maria (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The tinnitus has become a common otological complaint. Another complaint is found in bearers of the tinnitus is the hyperacusis.Objective: Analyze the characteristics of tinnitus and hyperacusis in normal hearing individuals with associated complaints of tinnitus and hyperacusis.Method: 25 normal hearing individuals who complained of hyperacusis and tinnitus were surveyed in this form of cross-sectional study. They were questioned about the location and type of the tinnitus. The evaluation of the tinnitus was made using the Brazilian Tinnitus Handicap Inventory and acuphenometry. A questionnaire was made about the hyperacusis covering aspects such as: sounds considered uncomfortable, sensations in the presence of such sounds, and difficulty understanding speech in noise.Results: Of the 25 individuals, 64% were women and 36% men. Regarding tinnitus, 84% referred to bilateral location and 80% high pitch. The most common degree found was light (44%). The women presented tinnitus degree statistically superior to those of men. The strong intensity sounds and the reactions of irritation, anxiety and the need to move away from the sound were the most mentioned. From the analyzed individuals, 68% referred to difficulty understanding speech in noise and 12% reported using hearing protection. The most found frequencies at the acuphenometry were 6 and 8 KHz.Conclusion: Normal hearing individuals who complain of tinnitus and hyperacusis present mainly high pitch tinnitus, located bilaterally and light degree. The sounds considered uncomfortable were the high intensity ones and the most cited reaction to sound was irritation. The difficulty to understand speech in noise was reported by most of the individuals.
Keywords: hearing; tinnitus; hyperacusis; questionnaires